1, 4‐Disubstituted 1, 2, 3‐Triazole‐ and 1, 5‐Disubstituted 1, 2, 3‐Triazole–based Bis‐Sulfonamides in Selective Fluorescence Sensing of ATP. Issue 6 (24th February 2017) - Dey, Santu; Sarkar, Tanmay; Majumdar, Anupam; Pathak, Tanmaya; Ghosh, Kumaresh
Abstract: 1, 4‐ and 1, 5‐Disubstituted 1, 2, 3‐triazole scaffolds as surrogate of amide with large dipole moment have been utilized to access two isomeric naphthylthiourea‐based chemosensors1 and2 in appreciable overall yields. The easily synthesizable chemosensors1 and2 are designed to recognize anions and also to realize a comparative view on their sensing potentials. Different inorganic phosphates and a group of phosphorylated nucleosides such as ATP, ADP and AMP are selectively recognized by these chemosensors in semi aqueous system. The fluorometric study revealed that both the sensors sensed ATP selectively in CH3 CN/H2 O (4/1, v/v) by showing considerable increase in emission. 1, 4‐Disubstituted triazole‐based sensor1 has been established to be more effective than the 1, 5‐disubstituted triazole‐based sensor2 in selective sensing of ATP. Abstract : Between two isomeric naphthylthiourea‐based chemosensors1 and2, 1, 4‐disubstituted triazole‐based sensor1 has been established to be more effective than the 1, 5‐disubstituted isomer2 in selective sensing of ATP.